1993
DOI: 10.2527/1993.71123359x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing corn-soybean meal diets with microbial phytase linearly improves phytate phosphorus utilization by weanling pigs1

Abstract: Two experiments were conducted with weanling pigs to determine the effectiveness of a dietary supplement of Aspergillus niger phytase in improving the availability of phytate-P in corn-soybean meal diets without supplemental inorganic P. Experiment 1 consisted of two P and Ca balance trials and two feeding trials. Twelve pigs (8.18 +/- .44 kg BW) were housed individually in stainless steel metabolism cages. Six pigs received 750 phytase units (PU)/g of basal diet and the other six pigs received the basal diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
56
2
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(76 citation statements)
references
References 12 publications
12
56
2
6
Order By: Relevance
“…The reduced-nutrient diet supplemented with phytase promoted the best animal performance but did not differ significantly from the positivecontrol diet. These results are consistent with those obtained by Lei et al (1993), who also found positive effects of phytase supplementation on the weight gain of growing pigs. Many other studies have shown positive effects of phytase on the performance of pigs (Kies et al, 2006;Veum et al, 2006).…”
Section: Resultssupporting
confidence: 83%
“…The reduced-nutrient diet supplemented with phytase promoted the best animal performance but did not differ significantly from the positivecontrol diet. These results are consistent with those obtained by Lei et al (1993), who also found positive effects of phytase supplementation on the weight gain of growing pigs. Many other studies have shown positive effects of phytase on the performance of pigs (Kies et al, 2006;Veum et al, 2006).…”
Section: Resultssupporting
confidence: 83%
“…These results were also observed by Lei et al (1993) who assessed supplementation with phytase in rations based on corn and soybean meal and rice meal at the levels of 0, 250, 500, and 750 FTU/kg for growing pigs and also observed a linear effect on feed conversion. Different results were reported by Murray et al (1997) who also used rations formulated with different ingredients than those used in the present study and obtained increase in weight gain of pigs that consumed rations supplemented with 700 and 1000 FTY/kg with a low level of available phosphorus.…”
Section: Resultssupporting
confidence: 64%
“…However, the use of phytase can increase phosphorus retention by 50% and reduction in excretion by 42% (Lei et al, 1993).…”
Section: Anti-nutritional Factor Mode Of Action Methods Of Detoxificationmentioning
confidence: 99%